Microglial activation during epileptogenesis in a mouse model of tuberous sclerosis complex. (6th June 2016) - Zhang, Bo; Zou, Jia; Han, Lirong; Rensing, Nicholas; Wong, Michael
Summary: Objective: Tuberous sclerosis complex (TSC) is a genetic disorder, characterized by tumor formation in multiple organs and severe neurologic manifestations, including epilepsy, intellectual disability, and autism. Abnormalities of both neurons and astrocytes have been implicated in contributing to the neurologic phenotype of TSC, but the role of microglia in TSC has not been investigated. The objectives of this study were to characterize microglial activation in a mouse model of TSC, involving conditional inactivation of the Tsc1 gene predominantly in glial cells ( Tsc1 GFAP CKO mice), and to test the hypothesis that microglial activation contributes to epileptogenesis in this mouse model. Methods: Microglial and astrocyte activation was examined in Tsc1 GFAP CKO mice by ionized calcium binding adaptor molecule 1 and glial fibrillary acidic protein immunohistochemistry. Cytokine and chemokine expression was evaluated with quantitative polymerase chain reaction. Seizures were monitored by video–electroencephalography (EEG). The effect of minocycline in inhibiting microglial and astrocyte activation, cytokine expression, and seizures was tested. Results: Microglial cell number and size were increased in cortex and hippocampus of 3‐ to 4‐week‐old Tsc1 GFAP CKO mice, which correlated with the onset of seizures. Minocycline treatment prevented the increase in number and cell size of microglia in 4‐week‐old Tsc1 GFAP CKO mice. However, minocycline treatment had no effect on astrocyte proliferation and cytokine/chemokine expression and the progression of seizures in Tsc1 GFAP CKO mice. Significance: Microglia cell number and size are abnormal in Tsc1 GFAP CKO mice, and minocycline treatment inhibits this microglia activation, but does not suppress seizures. Microglia may play a role in the neurologic manifestations of TSC, but additional studies are needed in other models and human studies to determine whether microglia are critical for epileptogenesis in TSC.